Establish an allele-specific real-time PCR for Leishmania species identification - Yun Wu; Mengyuan Jiang; Shaogang Li; Nicholas R. Waterfield; Guowei Yang (BMC, 2022)
Abstract Background Leishmaniasis is a serious neglected tropical disease that may lead to life-threatening outcome, which species are closely related to clinical diagnosis and patient management. The current Leishmania species determination method is not appropriate for clinical application. New Leishmania species identification tool is needed using clinical samples directly without isolation and cultivation of parasites. Methods A probe-based allele-specific real-time PCR assay was established for Leishmania species identification between Leishmania donovani and L. infantum for visceral leishmaniasis (VL) and among L. major, L. tropica and L. donovani/L. infantum for cutaneous leishmaniasis (CL), targeting hypoxanthine-guanine phosphoribosyl transferase (HGPRT) and spermidine synthase (SPDSYN) gene with their species-specific single nucleotide polymorphisms (SNPs). The limit of detection of this assay was evaluated based on 8 repeated tests with intra-assay standard deviation < 0.5 and inter-assay coefficients of variability < 5%. The specificity of this assay was tested with DNA samples obtained from Plasmodium falciparum, Toxoplasma gondii, Brucella melitensis and Orientia tsutsugamushi. Total 42 clinical specimens were used to evaluate the ability of this assay for Leishmania species identification. The phylogenetic tree was constructed using HGPRT and SPDSYN gene fragments to validate the performance of this assay. Results This new method was able to detect 3 and 12 parasites/reaction for VL and CL respectively, and exhibited no cross-reaction with P. falciparum, T. gondii, B. melitensis, O. tsutsugamushi and non-target species of Leishmania. Twenty-two samples from VL patients were identified as L. donovani (n = 3) and L. infantum (n = 19), and 20 specimens from CL patients were identified as L. major (n = 20), providing an agreement of 100% compared with sequencing results. For further validation, 29 sequences of HGPRT fragment from nine Leishmania species and 22 sequences from VL patients were used for phylogenetic analysis, which agreed with the results of this new method. Similar results were obtained with 43 sequences of SPDSYN fragment from 18 Leishmania species and 20 sequences from CL patients. Conclusions Our assay provides a rapid and accurate tool for Leishmania species identification which is applicable for species-adapted therapeutic schedule and patient management. Graphical Abstract